2017
DOI: 10.1111/ggi.13153
|View full text |Cite
|
Sign up to set email alerts
|

Location of white matter changes and response to donepezil in patients with Alzheimer's disease: A retrospective and observational study

Abstract: Aim: The response to donepezil in patients with Alzheimer's disease varies, and it is important to identify the potential responder before therapy. Cerebral white matter changes (WMC) are frequently observed in older patients, and the effect of WMC on therapeutic response remains controversial. The present study aimed to investigate the relationships between the location of WMC, severe WMC and the response to donepezil. Results: There was no significant difference in demographic data between responder and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
2
5
0
Order By: Relevance
“…Our results demonstrate that WMHs in the cholinergic pathway play a more decisive role in determining responsiveness to AChEI treatment than do WMHs in general. Similar observations have been presented in the literature, with one study reporting that white matter lesions in the frontal lobe and basal ganglia signi cantly reduced responsiveness to AChEI treatment [12]. Mounting evidence suggests links between the distribution or location of WMHs in the brain and cognition [20,22].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our results demonstrate that WMHs in the cholinergic pathway play a more decisive role in determining responsiveness to AChEI treatment than do WMHs in general. Similar observations have been presented in the literature, with one study reporting that white matter lesions in the frontal lobe and basal ganglia signi cantly reduced responsiveness to AChEI treatment [12]. Mounting evidence suggests links between the distribution or location of WMHs in the brain and cognition [20,22].…”
Section: Discussionsupporting
confidence: 81%
“…These markers have been employed in predicting responses to AChEIs, with inconsistent results. Some studies have indicated that hippocampal atrophy is a stronger determinant of responses to AChEI treatment [10,11], whereas others have concluded that WMHs are the stronger determinant [12,13]. An overview of ndings from relevant studies, including signi cant neuroimaging parameters, is presented in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, a retrospective study by Wu found that white matter changes in the frontal areas and the basal ganglia, evaluated on CT scans with the Age-Related White Matter Changes, were predictive of poor response to donepezil at 1 year. The author related this finding to the disruption of medial and lateral cholinergic pathways which originate from the basal forebrain, as well as to a reduction of the subcortical AChE due to the disruption of AchE-rich fibers (Wu et al, 2018 ). More studies are needed to clarify these contradictory findings, which may partially arise from the different scoring methods used.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some patient-or drug-related factors could affect treatment response. In this regard, response to AChEIs can be influenced by genetic polymorphism or concomitant vascular load/hippocampal atrophy of patients and by specific drug pharmacological properties [24,30,31]. On the contrary, the response to memantine could be less dependent on these factors [32].…”
Section: Discussionmentioning
confidence: 99%